THERAPY ACUPRESSURE AND MUROTTAL AL-QURAN ON THE PAIN INTENSITY AND ENDORPHIN URINE - enggal hadi kurniyawan; Joni Haryanto; Sriyono Sriyono; Kholid Rosyidi MN; Alfid Tri Afandi (Universitas Muhammadiyah Banjarmasin, 2018)
Most of the post-ORIF patients experience pain during wound care. Therapy analgesics and Complementary Alternative Medicine can be used to reduce pain during wound care. Acupressure and murottal Al-Qur'an are an alternative therapy that can be used to reduce pain. This study aims to explain the effect of acupressure and murottal Al-Quran in reducing the intensity of pain during wound care in patients post ORIF and increase levels of β-endorphins in urine. This research uses the Quasi-Experimental approach with pre-test-post-test. This research was conducted in dr. Soebandi Hospital. The sample of research was done by consecutive sampling technique, consist of 28 respondents. Data were collected using structured questionnaires, numeric pain scales, ELISA kits, and analyzed by ANOVA test. Acupressure, murottal Al-Quran, and a combination of acupressure and murottal Al-Quran have significantly reduced the intensity of pain during wound care in patients post ORIF. There is no intervention more effective between acupressure, murottal al-Quran and combination of acupressure and murottal al-Quran in reducing pain intensity. Acupressure, murottal Al-Quran, combined acupressure and murottal Al-Quran significantly can not increase β-endorphin level in urine. Acupressure, murottal Al-Quran, and a combination of acupressure and murottal Al-Quran are a good alternative therapy used to reduce pain intensity during wound care in patients post-ORIF but this intervention still can not increase β-endorphin in urine.